Analysis Of Mineral Types And Contents Of Copper (Cu) And Lead (Pb) In Copper Mining Area In Wetar Island - Male, Yusthinus T.; Bijang, Catherina M.; Naharuik, Sintia (Program Studi Di Luar Kampus Utama Universitas Pattimura, 2020)
The research to determine content of metal Cu and Pb in six samples (three ore rocks and three waste rocks) in the copper mining area on Wetar Island. The results showed that the highest concentration of Cu metal for ore rocks was in the first sample (MS KK) of 106,800 ppm and the smallest Cu concentration was in the third sample (PBx 1 KK) of 411 ppm. While the largest concentration of Cu metal waste rock is the first sample (Vol 1 KK) is 1.894 ppm and the smallest Cu metal concentration is in the second sample (BA 1 KK) is 310 ppm. As for the concentration of metal Pb in the largest ore rocks is in the first sample (MS KK) of 9,890 ppm, the small metal concentration of Pb is in the third sample (PBx 1 KK) is 660 ppm and the concentration of metal Pb for waste rock is found only in the first sample (Vol 1 KK) with a concentration of 1,631 ppm. This study shows that Wetar Island contains high copper and lead deposits.